2021
DOI: 10.1097/cce.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Doppler Measurement Variability in Functional Hemodynamic Monitoring: An Analysis of 17,822 Cardiac Cycles

Abstract: OBJECTIVES: Carotid Doppler ultrasound is used as a measure of fluid responsiveness, however, assessing change with statistical confidence requires an adequate beat sample size. The coefficient of variation helps quantify the number of cardiac cycles needed to adequately detect change during functional hemodynamic monitoring. DESIGN: Prospective, observational, human model of hemorrhage and resuscitation. SETTING: Human physiology laboratory at M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
1
20
2
Order By: Relevance
“…The U.S. Food and Drug Administration (FDA) cleared, 4 MHz Doppler ultrasound (Fig. 1 ) (Flosonics Medical, Sudbury, Canada) was placed and the ccFT, maximum and power-weighted, i.e., centroid, VTIs were captured [ 6 , 8 10 ].
Fig.
…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…The U.S. Food and Drug Administration (FDA) cleared, 4 MHz Doppler ultrasound (Fig. 1 ) (Flosonics Medical, Sudbury, Canada) was placed and the ccFT, maximum and power-weighted, i.e., centroid, VTIs were captured [ 6 , 8 10 ].
Fig.
…”
Section: Main Textmentioning
confidence: 99%
“…Yet measuring SV change (SV ∆ ) is clinically challenging, so surrogates like the common carotid artery Doppler pulse have been proposed [ 3 , 4 ] with some conflicting data [ 5 ]. We contend that statistically-inadequate beat sampling coupled with variation introduced by the respiratory cycle are important arbiters of inconsistent clinical research [ 6 ]. To rectify the shortcomings of handheld examinations, we developed a wireless, wearable Doppler ultrasound [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we believe that the described experimental paradigm is promising because it illustrates that averaging more beats in the carotid artery improves its relationship with the LVOT VTI. We have previously shown that the inherent physiological variation in the ccVTI that is induced by the respiratory cycle increases the sample size of cardiac cycles required to detect change with statistical confidence [ 15 ]. Thus, analyzing the relationship between the carotid artery and left ventricle with varying degrees of granularity may explain discordant clinical data [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, peripheral arteries have been exploited as surrogates of SV ∆ [ 10 ] as peripheral arteries, like the common carotid [ 11 , 12 ], are typically easier to insonate. Nevertheless, key drawbacks to hand-held Doppler measurements are human error [ 13 , 14 ] and relatively little guidance on the number of cardiac cycles to measure [ 15 ].…”
Section: Introductionmentioning
confidence: 99%